99mTc-Tetrofosmin uptake correlates with the sensitivity of glioblastoma cell lines to temozolomide - George Alexiou; Xanthi Xourgia; Paraskevi Gerogianni; Evrysthenis Vartholomatos; John Kalef-Ezra; Andreas Fotopoulos; Athanasios Kyritsis (World Journal of Nuclear Medicine)
99mTc-tetrofosmin (99mTc-TF) is a single-photon emission computed tomography tracer that has been used for brain tumor imaging. The aim of the study was to assess if 99mTc-TF uptake by glioblastoma cells correlates with their response to temozolomide (TMZ). We investigated the correlation of TMZ antitumor effect with the 99mTc-TF uptake in two glioblastoma cell lines. The U251MG cell line is sensitive to TMZ, whereas T98G is resistant. Viability and proliferation of the cells were examined by trypan blue exclusion assay and xCELLigence system. Cell cycle was analyzed with flow cytometry. The radioactivity in the cellular lysate was measured with a gamma scintillation counter. TMZ induced G2/M cell cycle arrest in U251MG cells, whereas there was no effect on cell cycle in T98G cells. Lower 99mTc-TF uptake was observed in U251MG cells that were exposed to TMZ compared to control (P = 0.0159). No significant difference in respect to 99mTc-TF uptake was found in T98G cells when exposed to TMZ compared to control (P = 0.8). With 99mTc-TF, it was possible to distinguish between TMZ-sensitive and resistant glioblastoma cells within 6 h of treatment initiation. Thus, 99mTc-TF uptake may consist a novel approach to assess an early response of glioblastoma to chemotherapy and deserves further investigation.